Proximate Analysis of Papain Enzyme-Supplemented Feed and Its Effects on Protein Efficiency Ratio and Feed Utilization Efficiency in Freshwater Crayfish (Cherax quadricarinatus) - Indra G. Ahmad; Arafik Lamadi; Rivaldi Kalapati; Mita Alvionita; Iin Susilawati Lantu (Jurnal Ilmiah Samudra Akuatika, 2026)
Papain is a proteolytic enzyme extracted from unripe papaya (Carica papaya) fruit and functions as a catalyst in the hydrolysis of proteins into simpler compounds. In aquaculture production, feed costs account for approximately 60–70% of total production expenses, highlighting the need for high-quality feed with enhanced utilization efficiency. This study aimed to analyze the proximate composition of feed supplemented with papain enzyme and to evaluate its effects on feed utilization efficiency (FUE) and protein efficiency ratio (PER) in freshwater crayfish (Cherax quadricarinatus). The feeding trial was conducted at UKM Kasih Karunia, Bube Village, Suwawa District, Bone Bolango Regency, Gorontalo, Indonesia. The study employed an experimental research design consisting of two treatments and three replications. The results showed that feed supplemented with 3.5% papain enzyme contained 41.10% crude protein, 20.35% moisture content, 2.71% crude fat, 6.35% crude fiber, 36.00% nitrogen-free extract (NFE), and 13.84% ash content. Furthermore, the feed utilization efficiency of the papain-supplemented diet reached 49.47%, which was considerably higher than that of the control diet without papain supplementation, which recorded an FUE value of 16.32%. These findings suggest that the inclusion of 3.5% papain enzyme in feed improves its nutritional quality and significantly enhances feed utilization efficiency in freshwater crayfish (C. quadricarinatus), thereby demonstrating its potential as a feed additive for aquaculture applications.